Digital storytelling for 21st century learning: a study on pre-service teachers’ perception / Siti Fairuz Dalim … [et al.] - Dalim, Siti Fairuz; Muhamad Azliza, Nurul Zakiah; Zulkipli, Zulinda Ayu; Ibrahim, Norezan; Mohd Yusof, Mohammad Mubarrak (2018)
Digital Storytelling is one of the new pedagogical tools that calls upon students’ creativity and helps them to “learn by doing”. It is one of the important steps towards creating the 21st century learning environment as it promotes the integration of student-centered and technology-enriched learning environment for learners. Despite the many benefits that this learning tool has to offer, many educators are still reluctant to integrate this kind of technology in their classes which resulted in low implementation of this technology among the educators. Therefore, this study is intended to determine pre-service teachers’ experience and perceptions towards digital storytelling for 21st century skills in learning environment. A set of questionnaire has been distributed to 150 trainee teachers from the Faculty of Education in one of public universities in Malaysia. The result of this study reveals that preservice teachers’ have moderately experienced the use of digital storytelling in their learning (M=2.98; SD=1.332). The finding also showed that the pre-service teachers responded positively towards the use of digital storytelling in the classroom (M=3.94; SD=0.713). The correlation analysis further showed that, the pre-service teachers’ experience with digital storytelling has significantly given impact on their perception towards the implementation of this tool in teaching and learning process. Considering the many advantages of the digital storytelling towards the enhancement of 21st century skills among the younger generations, therefore more aggression steps need to be done to strengthen the teaching preparation programme in higher educational institutions. This is very important to ensure that the future teachers produced are well-equipped with all the teaching skills and technologies to educate the next millennial generations.